1979
DOI: 10.1039/c39790000639
|View full text |Cite
|
Sign up to set email alerts
|

The chromium–heavy group 5 donor bond: a comparison of structural changes within the series [Cr(CO)5(XPh3)](X = P, As, Sb, or Bi)via their X-ray crystal structures

Abstract: Accurate X-ray data for [Cr(CO),(XPh,)] (X = As, Sb, or Bi) when compared with data for [Cr(CO),PPh,] show significant variations in C-X-C and Cr-X-C bond angles as well as in Cr-X distances consistent with increasing s-orbital participation in Cr-X bonding down the series X = P < X = As < X = Sb < X = Bi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 2 publications
2
18
0
1
Order By: Relevance
“…In fact the mean C-Sb-C angles (1: 104.8(4)°) or mean C-Bi-C angles (2: 104.5(5)°, 3: 104.9(3)°, 4: 104.2(8)°) lie between 90°, the value expected for p 3 configuration at antimony and 109.5°for sp 3 hybridisation, closer to the latter. The tendency to widen the bond angles in pyramidal stibine, or bismuthine ligands through coordination is well documented, for instance for (Me 3 Si) 3 Sb (mean angle Si-Sb-Si 99.2°) and [(Me 3 Si) 3 SbCr(CO) 5 ] (mean Si-Sb-Si 103.6°) [10] or for Ph 3 Bi (mean C-Bi-C 93.9° [13]) and [Ph 3 BiM(CO) 5 ] (mean C-Bi-C M = Cr 102.6°, Mo 98.0°, W 98.9° [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact the mean C-Sb-C angles (1: 104.8(4)°) or mean C-Bi-C angles (2: 104.5(5)°, 3: 104.9(3)°, 4: 104.2(8)°) lie between 90°, the value expected for p 3 configuration at antimony and 109.5°for sp 3 hybridisation, closer to the latter. The tendency to widen the bond angles in pyramidal stibine, or bismuthine ligands through coordination is well documented, for instance for (Me 3 Si) 3 Sb (mean angle Si-Sb-Si 99.2°) and [(Me 3 Si) 3 SbCr(CO) 5 ] (mean Si-Sb-Si 103.6°) [10] or for Ph 3 Bi (mean C-Bi-C 93.9° [13]) and [Ph 3 BiM(CO) 5 ] (mean C-Bi-C M = Cr 102.6°, Mo 98.0°, W 98.9° [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier work we had found that t Bu 3 Sb [7] and t Bu 3 Bi [8] form thermally stable transition metal carbonyl complexes, which at the time were characterised by infrared, Raman and 1 H NMR spectroscopy. We have now reinvestigated these compounds in order to achieve a full characterisation and report here the crystal structures, 13 [11], Mo, W [12,13]), [FeCp-(CO) 2 …”
Section: Introductionmentioning
confidence: 98%
“…for [Cr(CO)5 (EPh 3)] going from Cr-P to Cr-As there is an increase of 0.08/~ [77], while for [WI z (CO)3 (Ph2ECH2 EPh2)2 ] the difference from E=P to E=As is up …”
Section: Metal Arsine Complexesmentioning
confidence: 86%
“…A series of pentacarbonyl chromium compounds with formula [(CO) 5 CrBiR 3 ] (R = CH 3 , C 2 H 5 , C 6 H 11 ) were reported by Fischer and Richter as part of a study of the relative basicity of the group 15 "ine" ligands [105]. The triphenylbismuthine analogue was prepared by Carty et al in a similar study [106]. Talay …”
Section: The Transition Metal Chemistry Of Bismuthine Ligandsmentioning
confidence: 97%